Prospects for Sustainable Tourism in Mountain Protected Areas: A Case Study of Southeastern Serbia - Anđelina Marić Stanković; Marina Vesić; Sanja Pavlović; Marija Bratić; Željko Anđelković; Ana Lukić (Mountain Research and Development)
This research analyzes the factors that influence tourist experiences in the mountainous protected areas of southeastern Serbia. Tourism encompasses all aspects of a destination that can attract visitors and affect their satisfaction during their stay. The study examines the demographic characteristics of visitors, their preferences, the quality of infrastructure, and the tourist resources that the regions offer. A total of 570 visitors were surveyed, of whom 526 completed valid questionnaires that focused on the mountain areas of southeastern Serbia, particularly the foothills of Vlasina. The questionnaire placed particular emphasis on specific elements that affect tourist satisfaction. Key findings indicate positive correlations between elements essential for sustainable tourism, determined using Spearman's correlation. A chi-square test showed that environmental awareness and local community engagement were strongly associated with higher levels of overall tourist satisfaction, and a Kruskal–Wallis test revealed that older visitors, on average, expressed a greater level of satisfaction with infrastructure elements compared with younger groups. By focusing on the mountainous protected areas of southeastern Serbia, this research provides valuable insights for managers aiming to enhance visitor satisfaction and improve the quality of future experiences in the region.